Unraveling the influence of grain boundaries on the mechanical properties of polycrystalline carbon nanotubes. (December 2017) - Alian, A.R.; Meguid, S.A.; Kundalwal, S.I.
Abstract: The ability to produce homogeneous defect-free carbon nanotubes (CNTs) represents a major challenge in terms of utility and cost. Specifically, the existence of grain boundaries (GBs) are ubiquitous in large diameter CNTs obtained by various large-scale growth methods and their effects on the mechanical properties of CNTs are not fully explored. Understanding the influence of the grain size and the GB orientation upon the mechanical behavior of CNTs is crucial for their functional and structural applications. The significance and novelty of the current work lies in its ability to establish the mechanical properties and the fracture behavior of CNTs containing grain boundaries of varied size, orientation and structure to an applied uniaxial load using comprehensive molecular dynamics simulations. A specially developed program, using Voronoi tessellation method and Delaunay triangulation, was implemented to generate the atomistic descriptions of the considered polycrystalline CNTs with a variety of GB morphology. Our results reveal that the mechanical performance of CNTs is significantly affected by the orientations of the GBs, diameter and temperature. In terms of the fracture strength, the resulting failure patterns indicate that the polycrystalline CNTs fail in a brittle fashion and that pentagon-heptagon defects along the GBs serve as crack nucleation sites. Graphical abstract: